The Effect of Carboxyhemoglobin on Subjective Complaints of Fish Smoking Workers in Penatarsewu Village, Sidoarjo - Elfrida Ilma Shofiana; Irwan Sulistio; Putri Arida Ipmawati; Rusmiati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Fish smoking activities generate substantial amounts of smoke from incomplete combustion, exposing workers to various air pollutants, including carbon monoxide (CO), which may lead to adverse respiratory health effects. Prolonged inhalation of CO can result in the formation of carboxyhemoglobin (COHb), reducing oxygen transport in the blood and potentially causing subjective health complaints such as cough, dizziness, nausea, and shortness of breath. In Penatarsewu Village, Sidoarjo, a major center of traditional fish smoking, a high prevalence of respiratory complaints among workers has been reported, yet evidence regarding the role of COHb in these complaints remains limited. Therefore, this study aimed to analyze the effect of carboxyhemoglobin levels on subjective complaints among fish smoking workers in Penatarsewu Village, Sidoarjo. This study employed an observational analytic design with a cross-sectional approach. The study population consisted of 57 fish smoking workers, from which 25 female workers were selected using purposive sampling. COHb levels were measured through laboratory blood analysis, while data on subjective complaints, age, duration of daily exposure, and tenure were collected through structured interviews. Data were analyzed using simple linear regression to assess the influence of COHb and other related factors on subjective complaints. The results showed that all respondents had COHb levels within normal limits (≤3.5%), with values ranging from 0.40% to 1.72%. Despite this, 92% of workers reported experiencing subjective respiratory complaints. Statistical analysis revealed that COHb levels and tenure did not significantly affect subjective complaints (p>0.05). In contrast, age (p<0.001) and duration of daily exposure (p=0.003) showed a significant association with subjective complaints. In conclusion, subjective respiratory complaints among fish smoking workers were significantly influenced by age and length of exposure rather than COHb levels. These findings highlight the importance of regulating working hours and considering workers’ age to reduce health risks associated with fish smoking activities.